Inventarisasi Serangga Hama dan Penyakit pada Berbagai Galur Tanaman Padi : Inventory of Insect Pests and Diseases in Various Rice Crops - Lina Budiarti; Jaenudin Kartahadimaja; Miranda Ferwita Sari; Destieka Ahyuni; Ni Siluh Putu Nuryanti; Dulbari Dulbari; Hidayat Saputra (J-Plantasimbiosa, 2022)
One of the limiting factors for increasing rice production is the level of pests and diseases that attack cultivated rice varieties. The purpose of this study was to determine the types of pests that attack several cultivated rice lines. This research was conducted in the Seed Teaching Farm of the Seed Technology Study Program, Department of Food Crops Cultivation, Lampung State Polytechnic. The research was carried out in August-December 2020. The treatment given was rice plant strains. The rice plant lines used in this study were assemblies of the Seed Technology Study Program at the State Polytechnic of Lampung, namely 14 New Type Rice Lines (PTB), namely Pandan Wangi (PW), Ciherang (CH), B1, B2, B3, B4, B7, D2, D3, F3, F4, H1, H4, K, and L2 with 2 superior varieties for comparison, namely Ciherang (CH) and Gilirang (Gil). Rice cultivation is done conventionally. Observations of plant pests and diseases were carried out at the age of the plant every 2 weeks after planting (WST) with an observation interval of 2 weeks. Observations were made by looking directly at 5 sample clusters. The pests found were Nilapharvata lugens, Sogatella furcifera, Lasus lanio, Cnaphalocrosis medinalis, Scirpophaga incertulas, Mice, Xanthomonas oryzae bacterial leaf blight. Keywords: Pests, Diseases, Rice Lines